Die wapen van die Suid-Afrikaanse Republiek - Beyers, Coenraad,b. 1893; Heyns, H. A; Kotze, D. J; Barnard, C. J.(Christian Johan) (Stellenbosch : Stellenbosch University, 2012)
Full text to be digitised and attached to bibliographic record.